2018
DOI: 10.1186/s13075-018-1752-3
|View full text |Cite
|
Sign up to set email alerts
|

The presence of anti-nuclear antibodies alone is associated with changes in B cell activation and T follicular helper cells similar to those in systemic autoimmune rheumatic disease

Abstract: BackgroundDiagnosis of systemic autoimmune rheumatic diseases (SARD) relies on the presence of hallmark anti-nuclear antibodies (ANA), many of which can be detected years before clinical manifestations. However, ANAs are also seen in healthy individuals, most of whom will not develop SARD. Here, we examined a unique cohort of asymptomatic ANA+ individuals to determine whether they share any of the cellular immunologic features seen in SARD.MethodsHealthy ANA− controls and ANA+ (ANA ≥1:160 by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 74 publications
(69 reference statements)
3
36
2
Order By: Relevance
“…We and others have previously shown that elevated levels of type I IFN are associated with symptomatic progression in ANS and UCTD [52, 53]. Here, we show that there is no association between type I IFN levels and fatigue and that fatigue does not predict symptomatic progression.…”
Section: Discussioncontrasting
confidence: 50%
“…We and others have previously shown that elevated levels of type I IFN are associated with symptomatic progression in ANS and UCTD [52, 53]. Here, we show that there is no association between type I IFN levels and fatigue and that fatigue does not predict symptomatic progression.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous work has suggested a strong association between the IGS and autoantibodies ( 22 ) and the association of dsDNA autoantibodies with increased plasma cells ( 61 ) and Tregs ( 62 ) by flow cytometry. Our findings demonstrate that it is not the IGS that is ancestry dependent per se, as previously reported ( 26 ), but the presence of autoantibodies to RNP/Sm and the increased combination of autoantibodies that is associated with ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…For measurement of interferon (IFN)-induced gene expression, total RNA was isolated from the whole peripheral blood archived in PAXgene tubes (Applied Biosystems) and gene expression was quantified by NanoString using a custom array (nanoString Technologies), as previously described [20]. Log 2 normalized expression levels of 5 IFN-induced ubiquitously expressed genes (EPSTI1, IFI44L, LY6E, OAS3, RSAD2) were then summed to generate a composite IFN5 score [21].…”
Section: Measurement Of Ifn-induced Gene Expressionmentioning
confidence: 99%